“Slavery of the Mind and “Mental Imprisonment” (1870) in the harem: the Bodiless Society, a de-gendered or gender-neutral emancipatory social space? - Irene Kamberidou (Opening presentation to the ‘Virtual Harem’ for the Consultation Workshop on Gender and Technology, European Commission – Information Society DG, Brussels, 28 June 2004 2004 [explanation of power structures, limits and lessons that can be drawn], 2004)
Kamberidou, I. (2004).  “Slavery of the Mind and “Mental Imprisonment” (1870) in the harem: the Bodiless Society, a de-gendered or gender-neutral emancipatory social space? Opening presentation  (10.30 -11.00) to the ‘Virtual Harem’ for the Consultation Workshop on Gender and Technology, European Commission – Information Society DG. Avenue de Beaulieu 31   6/30, 1160 Brussels, 28 June 2004    [explanation of power structures, limits and lessons that can be drawn]   M. 1.  in Apella, Includes Consultation Workshop on Gender and Technology report on presentations, along with Preliminary Agenda/first draft (before corrections) for Gender and Technology Consultation Workshop, European Commission, Brussels